2011
DOI: 10.1159/000333231
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of ‘Atypia of Undetermined Significance’ Interpretations for Thyroid Fine-Needle Aspirations Is Negatively Correlated with Histologically Proven Malignant Outcomes

Abstract: Objective: Cytopathologists’ usage patterns for ‘atypia of undetermined significance’ (AUS) in thyroid fine-needle aspiration (FNA) are not well understood. AUS rates over a 5-year period were analyzed to quantify variability and identify correlations with experience and histologic outcomes. Study Design: A retrospective review of thyroid FNAs from a tertiary-care hospital from 2005 to 2009 was performed. Results were compiled for individual cytopathologists, stratified by year, and correlated with histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 37 publications
6
54
3
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18] These same studies have also reported their respective rates of malignancy as ranging from 6% to 48% for cases classified as AUS/FLUS with available followup. [9][10][11][12][14][15][16][17][18][19] It was noted at the time of the National Cancer Institute State of the Science Conference that the original recommendations may need to be revisited. Recently published data suggest that there is still some variation in incidence and risk of malignancy for the AUS/FLUS category.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18] These same studies have also reported their respective rates of malignancy as ranging from 6% to 48% for cases classified as AUS/FLUS with available followup. [9][10][11][12][14][15][16][17][18][19] It was noted at the time of the National Cancer Institute State of the Science Conference that the original recommendations may need to be revisited. Recently published data suggest that there is still some variation in incidence and risk of malignancy for the AUS/FLUS category.…”
mentioning
confidence: 99%
“…It has also been previously suggested that the reported rates of malignancy may be elevated because they are calculated from a subset of nodules that were selected for surgery, and therefore do not account for an inherent selection bias. 18 By design, most patients with nodules classified as AUS/FLUS will have benign nodules and will not undergo surgical resection, and their outcomes will not be known. 25 Other possibilities for such wide variation in the rate of AUS/FLUS cases among laboratories include differences in diagnostic threshold, experience, preparation methods, and the availability of rapid onsite evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the published reports after the widespread use of BRSTC informed highly variable risk of malignancy ranging between 6 %-96,7% in this group (3)(4)(5)(6)(7)(8). The malignancy rate in AUS/FLUS category of our center was 45,8% and is placed centrally in previosly reported wide risk spectrum (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 75%
“…These studies often come from different medical centres, and the stains vary because of the need to collect a sufficiently large cohort. An overwhelming majority of researchers use Papanicolau stain [5,6,10,14,18,[20][21][22][23][24][25][26][27][28].…”
Section: Prace Oryginalnementioning
confidence: 99%